Réglementer au plus près des territoires: le cas de la ressource en eau en France - Sophie Liziard; Rémi Barbier; Sara Fernandez (VertigO)
In France, since the adoption of the 1992 water act, “water development and management schemes” (“Schémas d’aménagement et de gestion des eaux” or SAGE for their French acronym) elaborated by Local Water Committees (“Commissions locales de l’eau” or CLE for their French acronym) have gradually organized local governance of water and aquatic environments, with great geographical disparities. The 2006 water act modified the scope of SAGE. The act, indeed, made compulsory defining a set of legally binding rules. These rules complement the main document of the SAGE that specifies strategic priorities for a given hydraulic territory, objectives to be reached and the means to achieve them. CLE must define, in a local and concerted manner, coercive rules necessary to reach these major objectives. Almost fifteen years after their introduction, our study, based on a database of rules and statistical analyzes, investigates how CLE, a rather consensual mode of governance, have tackled their new regulatory power and adapted rules to local needs and conditions.